The frequency of the Investigated Units - Василенко, Ольга Вікторівна; Vasylenko, Olha V. (Vinnytsia Pedagogical University Khmelnitsky, Technological University of Podolia, 1999)
Тези присвячені визначенню основних характеристик фактору частоти лексичних одиниць. Thesis represent the main characteristics of the factor "frequency".
Keywords: frequency; частота; lexical unit; лексична одиниця